Beyond the conventional Renin Angiotensin System - Walmor De Mello (Frontiers Research Topics, 2014)
It is well known that the activation of the circulating renin angiotensin system is involved in cardiovascular pathology including hypertension, heart failure and is responsible for important organic changes induced by diabetes. Evidence is now available that independently of the classical system, there are local renin angiotensin systems in different organs including the heart, circulatory vessels, kidney and probably brain and that components of these local systems participate in important aspects of physiology and pathology. Of particular interest is the presence of an intracellular component-the so called intracrine renin angiotensin system, which seems related to regulation of several cellular functions. A discussion of the different aspects of this important topic is of relevance to cell biology, endocrinology, physiology and pathology and justify a comprehensive presentation to the scientific community organized by experts in their respective fields.